The Effects of Nocturnal Blood Pressure Paterns and Autonomic Alterations on Erectile Functions in Patients with Hypertension - Yuvanc, Ercan; Dogru, Mehmet Tolga; Simsek, Vedat; Kandemir, Hüseyin; Tuglu, Devrim (Urology Journal, 2019)
Purpose: Hypertension (HT) is known to be of the main risk factors for erectile dysfunction (ED). But non-dipping (<%10 drop in the night) of HT is not investigated truly. The aim of this study was to test the hypothesis that the non-dipper hypertensive patients are more prone to develop erectile dysfunction. Materials and Methods: This was a cross-sectional clinical study. 70 HT patients diagnosed by Ambulatory blood pressure monitoring (ABPM) were classified into 3 groups (No ED, mild to moderate and severe) according to their International Index of Erectile Function (IIEF) scores. All three groups were compared for their dipping status by ABPM, heart rate variability (HRV) by holter monitoring. Results: In our study non-dipper hypertensives had statistically more erectile dysfunction (P=0.004). Also severe ED patients with non-dipping pattern had decreased dipping blood pressure levels then those of ED(-) patients with non-dipping HT (P= .003)(Daytime Systolic/Nighttime Diastolic Blood Pressure= 0.8 ± 0.07 / 3.90 ± 1.5, respectively). LF/HF daytime/ nighttime in holter reflecting sympathetic overactivity (P< .001). Conclusion: Autonomic dysfunction especially sympathetic overactivity is associated with both non dipping pattern of HT and erectile dysfunction as a common pathologic pathway, besides there might be an association between ED and non dipping HT.